A comparative analysis of single-step and multi-step methods for producing magnetic activated carbon from palm kernel shells: Adsorption of methyl orange dye - Waluyo Joko; Rahmawati Farida Dwi; Izzulhaq Muhammad Ghozy; Purba Ibnu Tryansar; Kaavessina Mujtahid; Wibowo Wusana Agung; Pranolo Sunu Herwi; Buwono Haris Puspito; Septian Ardie; Adnan Muflih Arisa (Green Processing and Synthesis)
Synthetic dyes in wastewater present a challenging problem that requires special attention due to the high environmental risks, and magnetic adsorbents appear as promising alternatives to solve it. Magnetic activated carbons (MAC) were prepared by comparing single- and multi-step methods. Palm kernel shells were used as precursors, activated with ZnCl2, and then magnetized by adding a solution containing Fe3+ ions (FeCl3). Iron compound inclusion aims to enhance the effectiveness of activated carbon as an adsorbent for liquid waste. Fourier transform infra-red characterization showed that the functional groups detected on the activated carbon and MAC were O–H, C═O, C═C, C≡N, and C–O. The effect of preparation methods and dye concentration (10–30 mg·L−1) on adsorption and kinetics were investigated. Characterization showed that MAC prepared through multi-step pyrolysis (M-MAC) has larger pores, achieving an adsorption capacity of up to 6.953 mg·g−1 with a 28% dye removal efficiency, making it superior in adsorption performance. Furthermore, the adsorption data fitted well with the Redlich–Peterson isotherm model with R 2 = 0.9788 for M-MAC, while the adsorption kinetics agreed well with both the pseudo-first-order and pseudo-second-order models. Moreover, NaOH successfully recovered MAC with desorption efficiencies of up to 98.34%.